Phytic Acid Decreases Oxidative Stress and Intestinal Lesions Induced by Fumonisin B1 and Deoxynivalenol in Intestinal Explants of Pigs - Elisângela O. da Silva; Juliana R. Gerez; Miriam S. N. Hohmann; Waldiceu A. Verri; Ana Paula F. R. L. Bracarense (Toxins, 2019)
The purpose of the present study was to investigate the effects of phytic acid (IP6) on morphological and immunohistochemical parameters and oxidative stress response in intestinal explants of pigs exposed to fumonisin B1 (FB1) and/or deoxynivalenol (DON). The jejunal explants were exposed to the following treatments: vehicle, IP6 5 mM, DON 10 µM, FB1 70 µM, DON 10 µM + FB1 70 µM, DON 10 µM + IP6 5 mM, FB1 70 µM + IP6 5 mM, and DON 10 µM + FB1 70 µM + IP6 5 mM. The decrease in villus height and goblet cell density was more evident in DON and DON + FB1 treatments. In addition, a significant increase in cell apoptosis and cell proliferation and a decrease in E-cadherin expression were observed in the same groups. DON and FB1 exposure increased cyclooxygenase-2 expression and decreased the cellular antioxidant capacity. An increase in lipid peroxidation was observed in DON- and FB1-treated groups. IP6 showed beneficial effects, such as a reduction in intestinal morphological changes, cell apoptosis, cell proliferation, and cyclooxygenase-2 expression, and an increase in E-cadherin expression when compared with DON, FB1 alone, or DON and FB1 in association. IP6 inhibited oxidative stress and increased the antioxidant capacity in the explants exposed to mycotoxins.